DIGITAL BUSINESS REPORTING IS A KEY TO ENHANCE FINANCIAL REPORTING QUALITY – AN XBRL PERSPECTIVE - N, Abhishek; M L, Ashoka; Singh, Ambrish; Parameshwara; M S, Divyashree (International Journal of Research -GRANTHAALAYAH, 2022)
Communication of high-quality business and financial information to decision-makers helps to get clear insights on the business outlook and assists them in making timely decisions. Financial reporting acts as a media to disseminate the information of the business to various interested parties by providing operating and financial insights through financial statements, notes to accounts and other footnotes and narratives in the Annual Business Report (ABR). Today stakeholders of the business are very keen in getting both financial and non-financial information in a single report i.e., ABR. Therefore, the companies are required to communicate enhanced information in their ABR to facilitate and assist the stakeholders in their decision-making process. The method of dissemination of both business and financial information in a single ABR is EBR Model (Enhanced Business Reporting Model). The EBR model of communication is only possible by the application of XBRL (Extensible Business Reporting Language). The purpose of present paper is to analyze the impact of XBRL on the quality of financial reporting. For this purpose, the study analyzed the financial reporting pattern of 23 select companies in India through the analysis of their annual reports from 2005 to 2020. To derive valid conclusions Tukey test, dummy variable regression analysis techniques were employed and concluded that XBRL has made a significant impact on the quality of financial reporting of select companies.